Development of a low cost small sized in-pipe robot - Md Zin M.R.A.; Sahari K.S.M.; Saad J.M.; Anuar A.; Zulkarnain A.T. (Elsevier Ltd, 2023)
This thesis reports the process of design and development of a low cost small sized in-pipe inspection robot. Problem of a pipe inspection operation surfaces when the robot only has a limited coverage of the inner surfaces of the pipe. Moreover, current solutions are largely sized and are not appropriate for smaller sized pipelines. Feasibility study completed produced a set of design requirements to be met for the final design to be able to operate inside a pipeline with inner diameter ranging from 80 mm to 180 mm. The use of magnets was decided as an adhesion system to allow the robot a full range of motion inside the pipe. Technical analyses were completed in parallel with the design work to ensure the design remains up-to-date in case there are changes in the off-the-shelf components used. A prototype of the final design was fabricated. Tests completed successfully demonstrated the robot traversing vertically and upside down on ferromagnetic surfaces, further proving the feasibility of the motor selection analysis. Moreover, the final design prototype managed to successfully satisfy the main objective of the project by being able to fit in a pipe environment with inner diameter ranging from 80 mm to 180 mm. 2012 The Authors.